UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN MEDIA PUZZLE PADA MATA PELAJARAN PPKN DI KELAS 1 SD NEGERI 060912 MEDAN - Ria Nita Fitri; Marah Doly Nasution; Rismadani Purba (STKIP Subang, 2024)
This research aims to improve the learning outcomes of class 1 students at SD Negeri 060912 Medan by implementing the Problem Based Learning learning model with puzzle media. This type of research is Classroom Action Research (PTK) which is carried out in 2 cycles. Before entering cycle I, students are given a pre-cycle test first to determine the students' abilities. After carrying out the pre-cycle test, learning activities enter cycle I stage then proceed to cycle II stage. The subjects of this research were 1st grade students at SD Negeri 060912 Medan, totaling 21 students. The results of this research show that the learning outcomes of students using the Problem Based Learning model using puzzle media showed an increase in the learning outcomes of students who achieved completeness by 57.1%, then in cycle II students who achieved completeness also experienced an increase of 90.5%. From these results it can be concluded that from cycle I to cycle II there was an increase in completion by 33.4%. This shows that the application of the Problem Based Learning learning model using puzzle media can greatly improve students' results.